VCAM-1+ placenta chorionic villi-derived mesenchymal stem cells display potent pro-angiogenic activity. Issue 1 (December 2016) - Du, Wenjing; Li, Xue; Chi, Ying; Ma, Fengxia; Li, Zongjin; Yang, Shaoguang; Song, Baoquan; Cui, Junjie; Ma, Tao; Li, Juanjuan; Tian, Jianjian; Yang, Zhouxin; et al.
Abstract Introduction Mesenchymal stem cells (MSCs) represent a heterogeneous cell population that is promising for regenerative medicine. The present study was designed to assess whether VCAM-1 can be used as a marker of MSC subpopulation with superior angiogenic potential. Methods MSCs were isolated from placenta chorionic villi (CV). The VCAM-1+/− CV-MSCs population were separated by Flow Cytometry and subjected to a comparative analysis for their angiogenic properties including angiogenic genes expression, vasculo-angiogenic abilities on Matrigelin vitro and in vivo, angiogenic paracrine activities, cytokine array, and therapeutic angiogenesis in vascular ischemic diseases. Results Angiogenic genes, including HGF, ANG, IL8, IL6, VEGF-A, TGFβ, MMP2 and bFGF, were up-regulated in VCAM-1+ CV-MSCs. Consistently, angiogenic cytokines especially HGF, IL8, angiogenin, angiopoitin-2, μPAR, CXCL1, IL-1β, IL-1α, CSF2, CSF3, MCP-3, CTACK, and OPG were found to be significantly increased in VCAM-1+ CV-MSCs. Moreover, VCAM-1+ CV-MSCs showed remarkable vasculo-angiogenic abilities by angiogenesis analysis with Matrigelin vitro and in vivo and the conditioned medium of VCAM-1+ CV-MSCs exerted markedly pro-proliferative and pro-migratory effects on endothelial cells compared to VCAM-1− CV-MSCs. Finally, transplantation of VCAM-1+ CV-MSCs into the ischemic hind limb of BALB/c nude mice resulted in a significantly functional improvement in comparison with VCAM-1− CV-MSCs transplantation. Conclusions VCAM-1+ CV-MSCs possessed a favorable angiogenic paracrine activity and displayed therapeutic efficacy on hindlimb ischemia. Our results suggested that VCAM-1+ CV-MSCs may represent an important subpopulation of MSC for efficient therapeutic angiogenesis.